Platelets, Constant and Cooperative Companions of Sessile and Disseminating Tumor Cells, Crucially Contribute to the Tumor Microenvironment - Obermann, Wolfgang M. J.; Brockhaus, Katrin; Eble, Johannes A. (Frontiers in Cell and Developmental Biology, 2021)
Although platelets and the coagulation factors are components of the blood system, they become part of and contribute to the tumor microenvironment (TME) not only within a solid tumor mass, but also within a hematogenous micrometastasis on its way through the blood stream to the metastatic niche. The latter basically consists of blood-borne cancer cells which are in close association with platelets. At the site of the primary tumor, the blood components reach the TME via leaky blood vessels, whose permeability is increased by tumor-secreted growth factors, by incomplete angiogenic sprouts or by vasculogenic mimicry vessels. As a consequence, platelets reach the primary tumor via several cell adhesion molecules. Moreover, clotting factor VII from the blood associates with tissue factor that is abundantly expressed on cancer cells. This extrinsic tenase complex turns on the coagulation cascade, which encompasses the activation of thrombin and conversion of soluble fibrinogen into insoluble fibrin. The presence of platelets and their release of growth factors, as well as fibrin deposition changes the TME of a solid tumor mass substantially, thereby promoting tumor progression. Disseminating cancer cells that circulate in the blood stream also recruit platelets, primarily by direct cell-cell interactions via different receptor-counterreceptor pairs and indirectly by fibrin, which bridges the two cell types via different integrin receptors. These tumor cell-platelet aggregates are hematogenous micrometastases, in which also platelets and fibrin constitute a particular TME in favor of the cancer cells. Even at the distant site of settlement, the accompanying platelets help the tumor cell to attach and to grow into metastases. Understanding the close liaison of cancer cells with platelets and coagulation factors that changes the TME during tumor progression and spreading will help to curb different steps of the metastatic cascade and may help to reduce tumor-induced thrombosis.